Leaf proteome modulation and cytological features of seagrass Cymodocea nodosa in response to long-term high CO2 exposure in volcanic vents - Piro, Amalia (2021)
Seagrass Cymodocea nodosa was sampled off the Vulcano island, in the vicinity of a submarine volcanic vent. Leaf samples were collected from plants growing in a naturally acidified site, influenced by the long-term exposure to high CO2 emissions, and compared with others collected in a nearby meadow living at normal pCO2 conditions. The differential accumulated proteins in leaves growing in the two contrasting pCO2 environments was investigated. Acidified leaf tissues had less total protein content and the semi-quantitative proteomic comparison revealed a strong general depletion of proteins belonging to the carbon metabolism and protein metabolism. A very large accumulation of proteins related to the cell respiration and to light harvesting process was found in acidified leaves in comparison with those growing in the normal pCO2 site. The metabolic pathways linked to cytoskeleton turnover also seemed affected by the acidified condition, since a strong reduction in the concentration of cytoskeleton structural proteins was found in comparison with the normal pCO2 leaves. Results coming from the comparative proteomics were validated by the histological and cytological measurements, suggesting that the long lasting exposure and acclimation of C. nodosa to the vents involved phenotypic adjustments that can offer physiological and structural tools to survive the suboptimal conditions at the vents vicinity.